KEPUASAN KERJA SEBAGAI MEKANISME MEDIASI ANTARA DISIPLIN KERJA, LINGKUNGAN KERJA, DAN KINERJA KARYAWAN - Marwan Effendi; Vina Puji Rahayu; Andy Rustandy (Universitas Prof. Dr. Hazairin SH, 2026)
This study aims to examine the effects of work discipline and the work environment on employee performance through the mediating role of job satisfaction among employees of PT Hamada Logistik Indonesia. A quantitative research design was employed using a census survey involving all 62 employees of the company. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that work discipline has a positive and significant direct effect on employee performance, whereas the work environment does not have a significant direct effect on employee performance. However, both work discipline and the work environment significantly influence employee performance indirectly through job satisfaction. The study is limited to a single logistics company with a relatively small sample size; therefore, the findings should be generalized with caution. This study contributes to the human resource management literature by providing empirical evidence that job satisfaction serves as a mediating mechanism through which work discipline and the work environment influence employee performance in the logistics industry. The findings also provide practical insights for managers in designing integrated human resource policies that strengthen work discipline, improve the work environment, and enhance job satisfaction to achieve better employee performance.